2022
DOI: 10.5430/wjel.v12n6p71
|View full text |Cite
|
Sign up to set email alerts
|

English-Medium Instruction and Content Learning in Freshman Year: An Investigation of a Saudi University Students’ Challenges and Learning Strategies

Abstract: The present study investigates the challenges that science freshmen perceive in English-medium instruction at Prince Sattam bin Abdelaziz University in terms of language and learning as well as the frequency of relevant learning strategies employed by students. A questionnaire was used to collect data from 376 students enrolled in the First Year Program at Prince Sattam Bin Abdelaziz University, considering their gender, scientific tracks, and previous English exposure. Results reveals that females were less c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…This endangers workforce equity goals, as qualified women miss opportunities due solely to language barriers. While scholarships now fund more women in STEM programs domestically and abroad, language deficiencies undermine related degree and career prospects (Altheyab & Alalwi, 2022). Addressing proven socioeconomic benefits of female workforce participation is critical to realizing Saudi Arabia's Vision 2030 reforms (World Bank, 2020).…”
Section: Technical English Proficiency In Educational Settings and It...mentioning
confidence: 99%
See 1 more Smart Citation
“…This endangers workforce equity goals, as qualified women miss opportunities due solely to language barriers. While scholarships now fund more women in STEM programs domestically and abroad, language deficiencies undermine related degree and career prospects (Altheyab & Alalwi, 2022). Addressing proven socioeconomic benefits of female workforce participation is critical to realizing Saudi Arabia's Vision 2030 reforms (World Bank, 2020).…”
Section: Technical English Proficiency In Educational Settings and It...mentioning
confidence: 99%
“…Video-based instruction holds promise as an effective supplemental approach for building technical English proficiency. Previous research has demonstrated several benefits of incorporating videos into language education (Altheyab & Alalwi, 2022). According to dual coding theory, multimedia design engages both auditory and visual channels to facilitate deeper encoding and retrieval of information compared to verbal-only methods.…”
Section: Advantages Of Video-based Learning In Technical English Acqu...mentioning
confidence: 99%